A qualitative analysis of parental loss and family separation among youth in post-conflict Liberia. Issue 1 (2nd January 2017) - Levey, Elizabeth J.; Oppenheim, Claire E.; Lange, Brittany C. L.; Plasky, Naomi S.; Harris, Benjamin L.; Lekpeh, G. Gondah; Kekulah, Isaac; Henderson, David C.; Borba, Christina P. C.
ABSTRACT: Between 1989 and 2003, the Republic of Liberia experienced a brutal civil war. In 2008, the population was approximately 3.5 million people, and there were an estimated 340, 000 orphans. Nearly 6000 more children were orphaned by the Ebola epidemic from 2014–2015. The goal of this research was to explore the impact of parental loss, identify moderating factors, and consider interventions that could help vulnerable youth in post-conflict societies following the loss of a parent. Seventy-five young people (age 13–18 years) in Monrovia, the capital city of Liberia, were recruited in 2012. Semi-structured interviews were conducted, and demographic data were collected. Interviews were then transcribed and coded thematically. The loss of a parent or other primary caregiver had a significant impact on psychosocial and emotional health. The timing of the loss, strength of connection with the deceased parent, and relationship with surviving parent or substitute caregiver were all relevant factors. Children separated from living parents were functioning better than those whose parents were deceased. The case of Liberian children underscores the importance of early caregiver relationships and the difficulties children face when such relationships are disrupted. Children who did not experience stable early relationships suffered disconnection from their families and communities.